Mucositis-Induced Pain due to Barrier Dysfunction may have a Direct Effect on Nutritional Status and Quality of Life in Head and Neck Cancer Patients Receiving Radiotherapy - ATASOY, BESTE MELEK; AKDENİZ, ESRA (KARE PUBL, 2020)
OBJECTIVE To maintain the barrier function against mucositis-induced pain and to improve the nutritional status and quality of life in head and neck cancer patients during radiotherapy. METHODS All patients (n=30) used oral gel to reduce mucositis-induced pain. Patients were examined weekly for the severity of mucositis, pain and nutritional status. The quality of life parameters was measured at the beginning and at the end of treatment. There was no restriction for pain killers against mucositis. RESULTS The only significant factor affecting the severity and frequency of mucositis was the cumulative radiation dose (p<0.001). Despite the regular use of oral gel, weight loss was observed in 65% of the patients. There was no difference concerning the severity of mucositis, cumulative radiation doses, or mean dose of oral mucosa between patients with no risk or at risk, according to SGA. However, self-assessment pain scores were significantly better in the well-nourished group (p=0.05 vs. 0.015) with better scores for dry mouth (p=0.043), social eating (p=0.006), swallowing difficulties (p=0.001) and communication (p=0.049). CONCLUSION Supporting the barrier function alone does not help to reduce the severity and frequency of mucositis, nor the oral pain in high doses. Mucositis-induced pain may have a direct effect on malnutrition risk and quality of life in head and neck cancer patients. Powerful strategies are required to manage pain due to mucositis during curative radiotherapy.
Keywords: Head and neck cancer; hyaluronic acid; nutrition; polyvinyl prolidone; quality of life; radiotherapy; ORAL MUCOSITIS; VALIDATION; GELCLAIR; THERAPY